2021
DOI: 10.1093/infdis/jiab144
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antimicrobial Susceptibility Profile inSalmonellaTyphi andSalmonellaParatyphi A: Presenting the Current Scenario in India and Strategy for Future Management

Abstract: Background Systematic studies to estimate the disease burden of typhoid and paratyphoid in India are limited. Therefore, a multicenter study on the Surveillance of Enteric Fever in India was carried out to estimate the incidence, clinical presentation, and antimicrobial resistance (AMR) trend. The data presented here represent the national burden of AMR in Salmonella Typhi and Salmonella Paratyphi A. Methods Antimicrobial sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…In contrast, more than 98% of the Salmonella Paratyphi A isolates were nonsusceptible to fluoroquinolone. This was likely driven by overtreatment and irrational use of quinolones to treat enteric fever all over South Asia and is often mediated by single point mutations in quinolone-resistance determining region (QRDR) [33][34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, more than 98% of the Salmonella Paratyphi A isolates were nonsusceptible to fluoroquinolone. This was likely driven by overtreatment and irrational use of quinolones to treat enteric fever all over South Asia and is often mediated by single point mutations in quinolone-resistance determining region (QRDR) [33][34][35][36][37].…”
Section: Discussionmentioning
confidence: 99%
“…To date, there is only one published report of a ceftriaxone resistant Paratyphi A isolate and that was detected in the UK from a Bangladeshi traveler [38]. Other studies also found no ceftriaxone resistance in Salmonella Paratyphi A [29,32,34,36]. Examination of minimum inhibitory concentration depicted a slightly increasing trend, but the average MIC is still 32 folds lower than the MIC required to render it completely resistant to ceftriaxone.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, fluoroquinolone non-susceptibility (FQNS) was high amongst S . Paratyphi A in South Asia, with FQNS strains from the SEFI collection accounting for 98% of all isolates [20].…”
Section: Discussionmentioning
confidence: 99%
“…Though MDR phenotypes were observed in a few S. Paratyphi A strains from the global collection, the plasmid was eventually lost during the evolution due to the greater fitness of antibioticsensitive strains [12]. On the contrary, fluoroquinolone non-susceptibility (FQNS) was high amongst S. Paratyphi A in South Asia, with FQNS strains from the SEFI collection accounting for 98% of all isolates [20]. The FQNS S. Paratyphi A were predominantly single QRDR mutant (gyrA-S83F) and distributed across the dominant phylogenetic lineages (A, C and F).…”
Section: Mutations In O:2-antigen Biosynthesis Genesmentioning
confidence: 99%
“…Enteric fever and especially typhoidal Salmonella endemic to South and Southeast Asia and sub-Saharan Africa require continuous monitoring where changing resistance trends have been reported due to fluoroquinolones and cephalosporins ( 16 , 17 ). Drug-resistant bacteria such as third-generation cephalosporin-resistant E. coli , carbapenem-resistant A. baumannii , fluoroquinolone-resistant E. coli , carbapenem-resistant K. pneumoniae , and third-generation cephalosporin-resistant K. pneumoniae represent serious challenges in patient management, especially in critically ill patient with comorbidities ( 3 , 4 , 7 , 11 , 14 ).…”
Section: Introductionmentioning
confidence: 99%